2014
DOI: 10.1186/cc13719
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia attenuates ventilator-induced diaphragm atrophy and modulates dysfunction

Abstract: IntroductionDiaphragm weakness induced by prolonged mechanical ventilation may contribute to difficult weaning from the ventilator. Hypercapnia is an accepted side effect of low tidal volume mechanical ventilation, but the effects of hypercapnia on respiratory muscle function are largely unknown. The present study investigated the effect of hypercapnia on ventilator-induced diaphragm inflammation, atrophy and function.MethodsMale Wistar rats (n = 10 per group) were unventilated (CON), mechanically ventilated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
1
13
1
Order By: Relevance
“…Sasson et al [24] also reported that positive end-expiratory airway pressure does not aggravate VIDD in rabbits [24]. Schellekens et al [25] reported that hypercapnea partly protects the diaphragm against the adverse effects of MV in a rat VIDD model. This study had the limitation that although mice ventilated at higher tidal volume had greater diaphragm weakness than those ventilated at lower tidal volume or controls, there were no other differences in the results of pulmonary function test, histological evaluation, or biochemical evaluation between groups.…”
Section: Discussionmentioning
confidence: 97%
“…Sasson et al [24] also reported that positive end-expiratory airway pressure does not aggravate VIDD in rabbits [24]. Schellekens et al [25] reported that hypercapnea partly protects the diaphragm against the adverse effects of MV in a rat VIDD model. This study had the limitation that although mice ventilated at higher tidal volume had greater diaphragm weakness than those ventilated at lower tidal volume or controls, there were no other differences in the results of pulmonary function test, histological evaluation, or biochemical evaluation between groups.…”
Section: Discussionmentioning
confidence: 97%
“…An experimental study in rats suggests that hypercapnia may protect against this problem [26]. Here, diaphragm myofiber myosin concentration was significantly increased compared with controls; in addition, tumor necrosis factor-a, interleukin-1b, and keratinocyte-derived chemokines were all significantly decreased in diaphragm homogenates of hypercapnia animals.…”
Section: Key Pointsmentioning
confidence: 89%
“…In this regard, piglets ventilated with increased dead space to achieve moderate hypercapnic acidosis (pCO 2 55-70 mmHg) showed preserved diaphragmatic force production after 72 h of mechanical ventilation [49]. A similar level of hypercapnia induced by adding inspired CO 2 also attenuated several aspects of VIDD in rats [50]. The cellular mechanisms underlying the improvements associated with hypercapnia are yet to be elucidated but likely involve anti-inflammatory and/or antioxidant effects.…”
Section: Interacting Factorsmentioning
confidence: 94%